Bowel obstruction due to tuberculosis band: A case report and review of the literature - Lafkih Oussama; Ouchane Mohamed; Saad Rifki El Jai; Hajri Amal; Errguibi Driss; Boufettal Rachid; Farid Chehab (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
Peritoneal tuberculosis accounts for 0.1-0.7% of all tuberculosis patients, the clinical signs are non-specific apart from a complication; The incidence of intestinal obstruction due to tuberculosis bands from 12% to 60%. Tuberculosis can affect any part of the body, but the abdomen is one of the most common sites after the lungs, The clinical presentation of abdominal tuberculosis is usually nonspecific and, therefore, often leads to a delay in diagnosis and thus the development of complications such as intestinal obstruction, Imaging plays an important role in the positive diagnosis of the occlusion. We report the case of a 61-year-old patient with no particular pathological history admitted to the emergency room with a bowel obstruction syndrome which the surgical exploration found a bowel obstruction on a primary tuberculosis band.